Abu Al-Hasan â€˜Ali Bin Ibrahim Al-Qummi and the Accusation of TahrÄ«f Al-Qurâ€™Än in Books of Shia Muslims: a Study on the Book Tafsir Al-Qummi - Haq, Muhammad Itsbatul; Halim, Abd. (IAIN Surakarta, 2021)
One of the most principal sources of Sunni-Shia conflict is theÂ claim aboutthe presence of'tahrÄ«f Al-Qur'an', or the distortion in the Qur'an, in many Shia literatures of Qur'an exegesis books.Â The claim ends in causing many Shia Muslims to suffer discrimination. For example, they are believed to have a different version of the Qurâ€™an and the doctrin ofÂ taqiyyahwith which they the true nature of their belif. This study focuses on the works ofÂ Abu al-Hasan â€˜Ali bin Ibrahim al-QummiÂ which are considered to be the main reference for accusing Shia Muslims of distorting some Qurâ€™anic verses(tahrÄ«f).Â This study aims to review the thought ofÂ al-QummiaboutÂ tahrÄ«f al-Qurâ€™anas he claimed.Â This is library research using content analysis.The research found thatÂ al-Qummiwhen developing the concept ofÂ 'tahrÄ«f Al-Qur'an'focused on exegetical exercises, not on actual distortion of the Qurâ€™anic texts.This finding was based on the fact that the term â€˜tahrifâ€™ which that some classical ulema (figures) of Shia Muslims made did not deal with distortion of the Qurâ€™anic verses (the corruption of texts), but with Qurâ€™an interpretations which contradict the intended meaning of the Qurâ€™anic verses (the corruption of meaning).